Procurators, Priests and Clerics: Male Leadership of the Beguinage of St. Elizabeth of Valenciennes in the Thirteenth and Fourteenth Centuries - Huanan Lu (Religions)
This study examines the distinctive male leadership—comprising procurators, parish priests, and chaplains—of the beguinage of St. Elizabeth in Valenciennes during the thirteenth and fourteenth centuries. Contrary to the majority of beguine communities in the southern Low Countries, where leadership appointments were dictated by religious or secular authorities, this community was entitled to elect its male administrators autonomously. The elected were generally influential figures in local religious and secular affairs and maintained a close relationship with the comital family of Hainaut. The analysis will demonstrate how this politically embedded ecclesiastical framework not only ensured doctrinal legitimacy but also mediated conflicts between secular lords and church authorities, thus enabling the community’s survival amid accusations of heresy and institutional repression. By examining the electoral criteria and functional specialization of male leaders, and their interactions with self-governed beguines, this research tries to offer a new perspective on the complex governance strategies of the medieval beguine movement.